Digital Reputation as a Protected Economic Interest under Indonesian Criminal Law - Evi Retno Wulan; Arief Budiman (LPPM of NAROTAMA UNIVERSITY, 2026)
The rapid expansion of Indonesia’s digital economy has transformed online reputation into a measurable economic asset for Micro Small and Medium Enterprises, as algorithm based rating systems directly determine visibility, consumer trust, and revenue sustainability. Despite its growing economic significance, the juridical status of digital reputation within Indonesian criminal law remains underdeveloped. This article examines whether online review extortion may be prosecuted under Law Number 1 Year 2023 concerning the Criminal Code and Law Number 11 Year 2008 concerning Electronic Information and Transactions as amended by Law Number 1 Year 2024. Using a normative juridical method with systematic and teleological interpretation, the study analyzes the structural elements of extortion, including unlawful threat, intent, causality, attempt, participation, and corporate liability, in the context of algorithm based reputational manipulation. The analysis demonstrates that Articles 482 and 483 of the Criminal Code, together with Article 27B of the Electronic Information and Transactions Law, provide a normative basis to prosecute digital coercion when reputational harm is conditionally linked to economic demand. However, neither statute explicitly recognizes digital reputation as an independent protected economic interest. This normative silence creates interpretative ambiguity and risks inconsistent enforcement. This article contributes to criminal law doctrine by conceptualizing digital reputation as a legally relevant economic interest within the framework of economic autonomy protection. Strengthening doctrinal clarity is therefore essential to ensure legal certainty, enhance deterrence, and reinforce the integrity of Indonesia’s digital economic governance.